Examining the Moderating Role of Religiosity on the Influence of Accountability, Income, and Knowledge on Interest in Cash Waqf Linked Sukuk - Lia Fitriani; Mulia Saputra; Muhammad Arfan (Proceeding International Conference on Accounting and Finance, 2025)
This study aims to examine the effect of waqf institution accountability, wakif income, and waqf knowledge on waqf interest through the Cash Waqf Linked Sukuk (CWLS) scheme, considering religiosity as a moderating variable. Using a quantitative approach, this study involved a sample of 50 CWLS waqf in Indonesia, and tested the hypothesis using the Moderated Regression Analysis (MRA) method. The results revealed that accountability, income, and religiosity significantly influenced waqf interest in participating in CWLS. Income showed the greatest influence, emphasizing the importance of financial capacity in increasing waqf involvement. In addition, religiosity acted as a moderator that strengthened the influence of accountability and income on waqf interest. In contrast, waqf knowledge did not have a significant influence, indicating that information alone is not enough without strong religious beliefs or values. These findings support the Theory of Planned Behavior in the context of waqf-based social finance, and highlight the importance of religious values and financial factors in encouraging public participation in innovative Islamic financial instruments such as CWLS.